(untitled) (Research, Society and Development, 2020)
Ovarian cancer is the eighth cause of death by cancer in women worldwide. The objective of this study was to analyze trends in the Brazilian ovarian cancer mortality and the relation to age, schooling, and race. Data was collected in the Brazilian Mortality Information System (SIM), from 2006 to 2016. The polynomial regression model was used for the trends analysis, a significant trend was considered when the estimated model obtained a p-value <0.05. Ovarian Cancer caused 34,003 deaths in Brazilian women in this period, the mortality rate (MR) was 0.46 per 100.000 women aged less than 40; 4.2 in women aged between 40 – 59; 12.2 in women aged between 60 – 79 and 19.4 in women 80 years old or more. About Race, 65% were White, others were declared as Black, Asian, Mixed-race, or Indigenous. Only 26% had 8 years or more of schooling. Mortality rates from ovarian cancer seemed to be rising in Brazil, the major increase happened in the South, the Southeast, and the Middle-West Regions. Women aged between 40 to 59 had the most significant increase. Politics are needed to facilitate the Brazilian population’s access to health services, consequently minimizing the time to diagnose and start the treatment. Research about mortality rates could help health workers identify gaps in knowledge and consequently decrease the magnitude of the disease.